Spatial Variation of Leaf Optical Properties in a Boreal Forest Is Influenced by Species and Light Environment - Atherton, Jon; Olascoaga, Beñat; Alonso, Luis; Porcar-Castell, Albert (Frontiers in Plant Science, 2017)
Leaf Optical Properties (LOPs) convey information relating to temporally dynamic photosynthetic activity and biochemistry. LOPs are also sensitive to variability in anatomically related traits such as Specific Leaf Area (SLA), via the interplay of intra-leaf light scattering and absorption processes. Therefore, variability in such traits, which may demonstrate little plasticity over time, potentially disrupts remote sensing estimates of photosynthesis or biochemistry across space. To help to disentangle the various factors that contribute to the variability of LOPs, we defined baseline variation as variation in LOPs that occurs across space, but not time. Next we hypothesized that there were two main controls of potentially disruptive baseline spatial variability of photosynthetically-related LOPs at our boreal forest site: light environment and species. We measured photosynthetically-related LOPs in conjunction with morphological, biochemical, and photosynthetic leaf traits during summer and across selected boreal tree species and vertical gradients in light environment. We then conducted a detailed correlation analysis to disentangle the spatial factors that control baseline variability of leaf traits and, resultantly, LOPs. Baseline spatial variability of the Photochemical Reflectance Index (PRI) was strongly influenced by species and to a lesser extent light environment. Baseline variability of spectral fluorescence derived LOPs was less influenced by species; however at longer near-infrared wavelengths, light environment was an important control. In summary, remote sensing of chlorophyll fluorescence has good potential to detect variation in photosynthetic performance across space in boreal forests given reduced sensitivity to species related baseline variability in comparison to the PRI. Our results also imply that spatially coarse remote sensing observations are potentially unrepresentative of the full scope of natural variation that occurs within a boreal forest.